Analysis of the Prevalence of Ponticulus Posticus on the Posterior Arch of the First Cervical Vertebra in Asymptomatic Orthodontic Patients - Drohomyretska, М. С.; Tkachenko, Ю. В.; Arshynnikov, Р. С. (Actual Dentistry, 2025)
The aim of the study: analysis of the prevalence of PP on digital lateral TRGs of asymptomatic orthodontic patients. Materials and methods. Eight hundred twenty-six digital lateral TRGs from patients aged 6 to 44 years who consulted at the Department of Orthodontics of the P. L. Shupyk National Institute of Health from 2022 to 2025 were analyzed. Of these, 179 lateral TRGs with radiological signs of PP on the posterior arch of the Atlas were selected. Results. PP was detected in 21.67% (179/826) of participants, of whom 65.36% (117/179) were female and 34.64% (62/179) were male. In the period of early mixed dentition, PP was found in 16.2% (29 out of 179 people); in the period of late mixed dentition, in 11.17% (20 out of 179 people); and in the period of permanent dentition, in 72.63% (130 out of 179 people). When distributing PP by types according to Nedelcu et al. (in descending order), type I was detected in 71 individuals (39.66%). Type III was observed in 43 individuals (24.02%); type V was observed in 30 individuals (16.76%); type II was observed in 25 individuals (13.97%); and type IV was observed in 2 individuals (1.12%). Conclusions: Although the study analyzed lateral TRGs in asymptomatic patients, PP can cause symptoms of vertebrobasilar insufficiency; therefore, at an orthodontic appointment, the doctor should be alert to this and involve neurologists in the diagnosis. PP is a relatively common variant of Atlas and accounts for almost 22% of the studied lateral TRGs; lateral TRGs can serve as a basic screening tool for detecting PP and diagnosing symptoms of head and neck pain.